2011
DOI: 10.1177/0363546510392710
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Arm and Shoulder Position on the Bear-Hug, Belly-Press, and Lift-Off Tests

Abstract: Clinicians may feel comfortable in using any of the 3 tests, depending on the patient, to isolate the function of the subscapularis as a single muscle. Furthermore, clinicians should not solely focus on a patient's arm position when administering an examination but also compare the affected arm to the contralateral shoulder when appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 27 publications
(95 reference statements)
0
19
0
Order By: Relevance
“…Pennock et al 31 reported that the level of subscapularis muscle activation was similar in the bear-hug, 2 belly-press, and lift-off tests; in these 3 tests, activation of the subscapularis was significantly greater than that of all other muscles. In the study of Bartl et al, 3 23 of 26 patients (88%) with fullthickness supraspinatus and subscapuraris tears had a positive belly-press test, and 20 (77%) had a positive liftoff test, while the remaining 6 (23%) could not perform the test due to restricted internal rotation.…”
Section: Discussionmentioning
confidence: 98%
“…Pennock et al 31 reported that the level of subscapularis muscle activation was similar in the bear-hug, 2 belly-press, and lift-off tests; in these 3 tests, activation of the subscapularis was significantly greater than that of all other muscles. In the study of Bartl et al, 3 23 of 26 patients (88%) with fullthickness supraspinatus and subscapuraris tears had a positive belly-press test, and 20 (77%) had a positive liftoff test, while the remaining 6 (23%) could not perform the test due to restricted internal rotation.…”
Section: Discussionmentioning
confidence: 98%
“…Assessments of the rotator cuff included clinical tests taken from standard texts [28]: the Jobe test [29] infraspinosus test [30], Lift-off test [31], external rotation lag sign [32], Neer impingement test [33] and Hawkins impingement test [34]. Individual characteristics recorded were age, sex, as well as dominant arm, the number of years of sports activities and the specific role played in the team.…”
Section: Methodsmentioning
confidence: 99%
“…With the elbow aligned with the trunk sagittally, the patient was then asked to push maximally against the abdomen by internally rotating the shoulder being tested without changing the position of the elbow. A positive test was indicated by unilateral weakness or an inability to perform the motion without elbow or other shoulder compensation 15,16 (Figure 1).…”
Section: Physical Examinationmentioning
confidence: 99%
“…Then, the patient was asked to maximally lift the hand off of the back by internally rotating the shoulder. A positive lift-off test was demonstrated by an inability to lift the hand off of the back or the use of the elbow or other components of the glenohumeral joint to perform the movement 15,16 (Figure 2).…”
Section: Physical Examinationmentioning
confidence: 99%
See 1 more Smart Citation